Midwifery-led antenatal pelvic floor muscle exercise intervention to reduce postnatal urinary incontinence: APPEAL research programme including a feasibility and pilot cluster RCT - Christine MacArthur; Debra Bick; Victoria Salmon; Ellie Jones; Jean Hay-Smith; Jon Bishop; Eleni Gkini; Karla Hemming; Sara Webb; Mark Pearson; Tim Coleman; Rohini Terry; et al. (NIHR Journals Library, 2024)
Background Antenatal pelvic floor muscle exercises are effective in reducing postnatal urinary incontinence. Midwives, however, lack training and confidence to promote these exercises and often do not provide information or support to women to do the exercises. Objectives Objectives were to: (1) investigate current antenatal care in relation to pelvic floor muscle exercise support from midwives for women; (2) develop an intervention to increase the likelihood of midwives supporting women to do pelvic floor muscle exercises during pregnancy; and (3) test the intervention in a feasibility and pilot cluster randomised controlled trial with numerous trial and process evaluation outcomes. Design Study designs included critical interpretive synthesis, ethnography and other methods (interviews, focus groups, behaviour change theory mapping, stakeholder and patient/public involvement activities) and piloting questionnaires to develop an intervention to test in a feasibility and pilot cluster randomised controlled trial. Clusters were community midwife teams. Setting Main setting: two National Health Service hospital trusts providing maternity care in Birmingham. Participants Participants included pregnant women and midwives. Pilot trial participants included women who gave birth during a prespecified month in study maternity units. Midwives participated in trial process evaluation. Interventions Midwives in teams randomised to the intervention were trained how to teach pelvic floor muscle exercises to women and support them in undertaking these exercises throughout pregnancy. Midwife teams allocated to control provided standard antenatal care. Main outcome measures Early-phase outcomes were whether current antenatal midwife care supported women to undertake pelvic floor muscle exercises, and a midwife pelvic floor muscle exercise training intervention. Main feasibility and pilot trial outcomes included return rates and associated intraclass correlation coefficient; whether midwives provided pelvic floor muscle exercise support to women during antenatal care; women's adherence to undertaking pelvic floor muscle exercises antenatally; and prevalence estimates of urinary incontinence at 10-12 weeks post partum. Other process outcomes included intervention midwives' confidence in pelvic floor muscle exercise knowledge and views on intervention delivery; women's views on pelvic floor muscle exercise support received; and control midwives' views on pelvic floor muscle exercises in standard care. Results The critical interpretive literature synthesis showed that current antenatal pelvic floor muscle support was constrained by numerous factors including women's and healthcare professionals' capacity to implement pelvic floor muscle exercises. Reform of healthcare policy and service delivery was recommended to provide opportunity to genuinely support women and healthcare professionals. Main findings of early-phase qualitative research showed that women and midwives 'know' that pelvic floor muscle exercises are important, but that midwives infrequently communicate to women the large 'gains' available from undertaking these exercises. There was lack of confidence among women and midwives on when and how to initiate discussion on pelvic floor muscle exercises and urinary incontinence. A systematic review of diagnostic tests for midwives to use to support women's practice of pelvic floor muscle exercises identified no available studies. Qualitative research with women and midwives, mapping to behaviour change theory, and stakeholder and patient/public involvement activities followed by a practice training event showed that the intervention should consist of five steps: raising the topic of incontinence and pelvic floor muscle exercises; screening for symptoms; teaching the exercises; reminding and supporting women to do the exercises; and knowing when and how to refer. Midwife training evaluation findings showed median positive change following training of 1 point (0-5 scale) for each of eight questions related to confidence about pelvic floor muscle exercise knowledge and teaching the exercises. In the cluster trial, 17 clusters were randomised and 95 midwives in intervention clusters were trained. Of 998 women included in the trial, 175 returned a questionnaire: 15.8% in intervention and 16.4% in control clusters. Based on women's responses to the post-partum postal questionnaire, 65% of those in intervention clusters said their midwife explained how to do pelvic floor muscle exercises compared to 38% of those in control clusters. Among women in intervention clusters, 50% undertook the exercises in a manner likely to improve symptoms compared to 38% of women in control clusters, and 44% of women in intervention clusters reported urinary incontinence compared to 54% in control clusters. Interviews with midwives and women generally supported trial findings and emphasised the importance of service change for ensuring time to implement the Antenatal Preventative Pelvic floor Exercises And Localisation intervention into antenatal appointments. Limitations There was a low questionnaire return rate. A definitive trial, which would have provided evidence of effectiveness not possible from a pilot trial, could not be undertaken because of changes to standard midwife antenatal care due to National Health Service England's new perinatal pelvic health service. Conclusions Training midwives to appropriately support women to undertake pelvic floor muscle exercises in pregnancy is feasible, acceptable and could improve exercise adherence and reduce post-partum urinary incontinence. Future work Implementation work with National Health Service England has begun. Study registration This study is registered as ISRCTN10833250. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research Programme (NIHR award ref: RP-PG-0514-20002) and is published in full in Programme Grants for Applied Research; Vol. 12, No. 9. See the NIHR Funding and Awards website for further award information. Plain language summary After having a baby, it is very common to leak urine. We know that pelvic floor muscle exercises, when done correctly during pregnancy, can help. The problem is that midwives lack confidence to teach, or do not always explain how to do pelvic floor muscle exercises very well. Even when they do, women may not do them as it is unclear why they should. By talking to many women, midwives and researchers, we developed a way of training midwives to teach and support women during pregnancy to do these exercises. After their training, we found that midwives knew more about pelvic floor muscle exercises and were more confident to teach and support women. To test how well the training worked, we did a pilot trial where midwife teams were randomly selected to be given this training or continue with usual antenatal care. We sent a questionnaire to women when their baby was 3 months old. This asked what advice and support their midwife had given them about pelvic floor muscle exercises during pregnancy, whether they did the exercises, and whether they leaked urine over the last 4 weeks. We found that more women who had antenatal care from a midwife who had been trained were told why and how to do pelvic floor muscle exercises, more of these women did these exercises, and not as many leaked urine. These consistent outcomes are promising, but it was only a pilot trial and not many women returned their questionnaire, so we cannot be certain of these results. We interviewed some women: most were pleased about getting help with pelvic floor muscle exercises and all wanted this help. We interviewed some of the trained midwives. They were keen to help women but said lack of time meant it could be difficult to fit teaching these exercises into antenatal appointments. We could not progress to doing a definitive trial because a new National Health Service perinatal pelvic health service is being set up. However, we have provided the training developed in this programme to many of the lead staff who are setting up the new services. Scientific summary Background A Cochrane Review published when planning this programme showed that antenatal pelvic floor muscle exercises (PFME) in women without urinary incontinence (UI) were effective in reducing postnatal UI.